Natural infection by Strongyloides stercoralis in Pithecia monachus (Primates, Pitheciidae). First report in Peru - Tantaleán V., Manuel (2018)
The objective of the present work was to identify nematodes obtained post mortem from the small intestine of Pithecia monachus bred in captivity in Iquitos, Peru. The identification was made observing the morphology and anatomy of the female specimens of the intestine of the host and of males and females obtained by culture. All specimens were identified as Strongyloides stercoralis. It is concluded that this species is found for the first time in a primate in Peru.